Lycium ferocissimum Miers en la Península Ibérica (Málaga, España). - Pérez Latorre, Andrés V.; Yus Ramos, Rafael; Dana Sánchez, Elías (Acta Botanica Malacitana, 2006)
Lycium ferocissimum Miers in the Iberian Peninsula (Malaga, Spain) Palabras clave. Lycium, Solanaceae, plantas invasoras, Andalucía, España. Key words. Lycium, Solanaceae, invading plants, Andalusia, Spain.